2017
DOI: 10.1093/jme/tjx208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatty Acid and Geraniol Repellent-Oil Mixtures Applied to Cattle on Blood Feeding and Reproductive Parameters in Field Populations of Haematobia irritans (Diptera: Muscidae)

Abstract: California pastured cattle were treated with 250 ml of a 15% mixture of fatty acids (C8-C9-C10) or 125 ml of 2% geraniol in a mineral oil carrier to assess impacts on horn flies, Haematobia irritans (L.) (Diptera: Muscidae) over two summers. Horn flies were netted from cattle every 3-4 d for 2 wk before treatment, 2 wk during treatment (four treatments, with flies collected before each treatment), and 2 wk after treatments ceased. Blood meal weights were estimated by hemoglobin assay of excised abdomens. Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Integration of push-pull strategies in the management of livestock pests is a viable option for controlling pest fly populations [90]. The identification of natural product compounds that successfully repel horn fly adults and the evidence of repellent effectiveness in the field [8][9][10][11][12][13][14], while short-lived, supports the pursuit of this tool as an option for non-pesticide fly control. A further understanding of horn fly chemosensory pathways will provide additional targets for pest control development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of push-pull strategies in the management of livestock pests is a viable option for controlling pest fly populations [90]. The identification of natural product compounds that successfully repel horn fly adults and the evidence of repellent effectiveness in the field [8][9][10][11][12][13][14], while short-lived, supports the pursuit of this tool as an option for non-pesticide fly control. A further understanding of horn fly chemosensory pathways will provide additional targets for pest control development.…”
Section: Discussionmentioning
confidence: 99%
“…The repellent effect of geranium, lemongrass, peppermint, catnip, geraniol, and coconut oil constituents have been documented against horn flies in a laboratory setting [8][9][10][11]. Further, on-animal, field evaluation of the repellency of medium chain length fatty acid derivatives and 2% geraniol against the horn fly suggested these compounds impacted the mating status of on-animal populations and were effective at reducing blood-feeding by female horn flies and at repelling older females [12][13][14]. While the duration of activity is currently limited and the desired response can require large quantities of compound, the results are promising.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Biorational compounds with repellent activity are potential alternatives to pyrethroids to prevent stable fly feeding on pasture cattle. [13][14][15] Repellent plant essential oils derived from catnip and geranium and fatty acid mixtures have demonstrated activity against biting flies. 13,16,17 A trial with catnip oil in a soybean and paraffin wax solution showed promising spatial repellency against stable flies.…”
Section: Introductionmentioning
confidence: 99%